AtOPT6 Protein Functions in Long-Distance Transport of Glutathione in Arabidopsis thaliana. (14th April 2018) - Wongkaew, Arunee; Asayama, Koki; Kitaiwa, Taisuke; Nakamura, Shin-Ichi; Kojima, Katsuhiro; Stacey, Gary; Sekimoto, Hitoshi; Yokoyama, Tadashi; Ohkama-Ohtsu, Naoko
Abstract: The involvement of the Arabidopsis oligopeptide transporter AtOPT6, which was previously shown to take up glutathione (GSH) when expressed in yeast cells or in Xenopus laevis oocytes, in GSH transport was analyzed using opt6 knockout mutant lines. The concentration of GSH in flowers or siliques was lower in opt6 mutants relative to wild-type plants, suggesting involvement of AtOPT6 in long-distance transport of GSH. The GSH concentration in phloem sap was similar between opt6 mutants and wild-type plants. These results, combined with earlier reports showing expression of AtOPT6 in the vascular bundle, especially in the cambial zone, suggest that AtOPT6 functions to transport GSH into cells surrounding the phloem in sink organs. The opt6 mutant plants showed delayed bolting, implying the importance of AtOPT6 for regulation of the transition from vegetative to reproductive growth. After cadmium (Cd) treatment, the concentration of the major phytochelatin PC2 was lower in flowers in the opt6 mutants and Cd was accumulated in roots of opt6 mutant plants compared with wild-type plants. These results suggest that AtOPT6 is likely to be involved in transporting GSH, PCs and Cd complexed with these thiols into sink organs.